Use of a pharmacy-based GP video consultation service: a mixed methods study. (28th September 2022) - Parsons, Joanne; Rahman, Sameur; Bryce, Carol; Atherton, Helen
Abstract: Background: Little is known about private general practice appointment services offered via video. This study aimed to explore which patients are using a video pharmacy-based general practitioner (GP) appointment service, including patterns of use, reasons for using the service, and satisfaction with the service. Methods: Descriptive statistics and parametric and nonparametric tests were used to conduct a retrospective cross-sectional analysis of routinely collected data on consultations, and postconsultation questionnaires. Interviews were conducted with patients and GPs. Results: A total of 7, 928 consultations were included in the analysis. More than half of appointments were booked for the same day, with lunchtime appointments being popular. The most common health condition was respiratory conditions, and 9% of consultations were used by patients using the service more than once. At least one prescription was issued in over half of all consultations. Overall, satisfactions of consultations were high. Conclusions: The characteristics of those patients using the video consultation service match data on who uses online services in general practice. This study shows that some patients are willing to pay to use this private service because they feel it is more convenient, NHS services do not have capacity to see them at the time they need, or they do not have access to regular GP services. Lay Summary: Over recent years, improvements in technology have made video and telephone general practitioner (GP) appointments more popular, and the Covid-19 pandemic has increased the need for these. There are lots of companies offering private GP appointments over video, but we do not yet know much about these, or why some people choose them over traditional GP appointments. This research aimed to find out which groups of people chose to use one private service that offers GP appointments over video in pharmacies, and why they chose to use it. The service has medical equipment (such as blood pressure monitor and camera) that can be used during the video GP appointment. Information was collected about 7, 928 appointments in the time the study looked at, and 10 GPs that provide appointments, and 9 patients that used the service were interviewed to find out how they felt about it. Patients using this service were satisfied with their appointment, and were satisfied with the Doctor they saw. Reasons they chose to use the service included that they could be seen quicker than their normal GP, or at a time that was more convenient to them.